Sequential feeding with diets varying in amino acid content for growing-finishing pigs - Silva, Welex Candido da [UNESP]; Reis Furtado Campos, Paulo Henrique; Santos, Luan Sousa dos; Veira, Alini Mari [UNESP]; Fraga, Alicia Zem [UNESP]; Hauschild, Luciano [UNESP] (Univ Sao Paolo, 2021)
This study aimed to evaluate the effects of daily phase feeding (DP) and sequential feeding (SEQ) on the feeding behavior, performance, and body composition of growing-finishing pigs. Sixty barrows at 29.7 +/- 2.8 kg body weight (BW) were assigned to one of four treatments: DP with a blended proportion of feeds A (high nutrient density) and B (low nutrient density) was adjusted to match 100 % of daily amino acid (AA) diet recommendations (DP100); a negative treatment, which matched 70 % of daily M diet recommendations (DP70); and two SEQ with a blend of feeds A and B, adjusted twice a day (at 00h00 and 12h00), to match 70 or 110 % of daily AA diet recommendations during two 12 h intervals: SEQ110-70 and SEQ70-110. DP70 and SEQ showed a lower feed consumption rate compared to DP100 (p < 0.05). Compare to DP100, pigs in both SEQ programs had a similar average daily feed intake (ADFI), average daily gain (ADG), feed efficiency ratio (G:F) and body fat and lean mass ( p > 0.05). SEQ110-70 and SEQ70-110 showed similar ADFI, ADG, G:F and body lean mass (p > 0.05). However, fat gain was greater in SEQ110-70 than in SEQ70-110 (p < 0.05). Overall, the SEQ program does not improve performance and body composition. Furthermore, feeding pigs a diet with a higher AA level during the first 12 h of the day and a lower AA level during the remainder of the day increases fat deposition.
Keywords: circadian rhythms; daily feeding phase; feeding techniques; precision feeding